Melting Behavior of Phase Change Material in a Solar Vertical Thermal Energy Storage with Variable Length Fins added on the Heat Transfer Tube Surfaces - Ramalingam Senthil; Aditya Patel; Rohan Rao; Sahil Ganeriwal (International Journal of Renewable Energy Development, 2020)
This paper investigates the melting behaviour of phase change material (PCM) in a vertical thermal energy storage system with provision of thin rectangular fins of uniform and variable lengths on the heat transfer tube surfaces. The selected PCM and heat transfer fluid (HTF) are paraffin wax and water, respectively. The HTF is passed through the helically coiled copper tube of 10 mm diameter to melt the PCM. The time required to complete the melting of PCM in the system with fins is found to be five hours, whereas for the system without fins it is five hours and forty minutes, for the same conditions of constant water temperature of about 70°C and flow rate of 0.02 kg/s. HTF tube with fins is observed to be more effective with a 13.33% faster rate of melting when compared to that of the HTF tube without fins. Such a fast charging process will be helpful in storing maximum energy within a short period/duration of time shorter duration in for solar thermal and heat recovery applications during lean production times. ©2020. CBIORE-IJRED. All rights reserved